2023
DOI: 10.3390/genes14091774
|View full text |Cite
|
Sign up to set email alerts
|

Non-Viral Episomal Vector Mediates Efficient Gene Transfer of the β-Globin Gene into K562 and Human Haematopoietic Progenitor Cells

Vassileios Lazaris,
Emmanouil Simantirakis,
Eleana Stavrou
et al.

Abstract: β-Thalassemia is a subgroup of inherited blood disorders associated with mild to severe anemia with few and limited conventional therapy options. Lately, lentiviral vector-based gene therapy has been successfully applied for disease treatment. However, the current development of non-viral episomal vectors (EV), non-integrating and non-coding for viral proteins, may be helpful in generating valid alternatives to viral vectors. We constructed a non-viral, episomal vector pEPβ-globin for the physiological β-globi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…SMAR vectors represent a promising alternative to traditional virusbased therapeutic vectors, as they can carry larger therapeutic genes with lower treatmentassociated toxicity than many viral vectors. In ground-breaking work, SMAR DNA vectors have been effectively used to genetically engineer haematopoietic progenitor cells with therapeutic genes [28][29][30] and to genetically correct a mouse model of blindness [31]. We built on this work with a recent study that demonstrated that gene augmentation of the 16 kb USH2A gene in zebrafish retinas using SMAR vectors, with transgene expression still detectable in vivo after 12 months [32].…”
Section: Introductionmentioning
confidence: 99%
“…SMAR vectors represent a promising alternative to traditional virusbased therapeutic vectors, as they can carry larger therapeutic genes with lower treatmentassociated toxicity than many viral vectors. In ground-breaking work, SMAR DNA vectors have been effectively used to genetically engineer haematopoietic progenitor cells with therapeutic genes [28][29][30] and to genetically correct a mouse model of blindness [31]. We built on this work with a recent study that demonstrated that gene augmentation of the 16 kb USH2A gene in zebrafish retinas using SMAR vectors, with transgene expression still detectable in vivo after 12 months [32].…”
Section: Introductionmentioning
confidence: 99%